2018
DOI: 10.1038/s41590-018-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of microbial viability via TLR8 drives TFH cell differentiation and vaccine responses

Abstract: Live attenuated vaccines are generally highly efficacious and often superior to inactivated vaccines, yet the underlying mechanisms of this remain largely unclear. Here we identify recognition of microbial viability as a potent stimulus for follicular helper T cell (T cell) differentiation and vaccine responses. Antigen-presenting cells (APCs) distinguished viable bacteria from dead bacteria through Toll-like receptor 8 (TLR8)-dependent detection of bacterial RNA. In contrast to dead bacteria and other TLR lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
175
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(182 citation statements)
references
References 84 publications
(107 reference statements)
6
175
0
1
Order By: Relevance
“…Others show that IL‐1β, produced by monocytes downstream of TLR signalling and inflammasome activation, induces differentiation of T follicular helper cells, which augment antibody production . Moreover, Ugolini et al . demonstrate that TLR8 engagement represents a mechanism via which CD14 + CD16 + monocytes selectively detect viable as opposed to dead microorganisms, and signal this via producing IL‐1β, which activates T follicular helper cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others show that IL‐1β, produced by monocytes downstream of TLR signalling and inflammasome activation, induces differentiation of T follicular helper cells, which augment antibody production . Moreover, Ugolini et al . demonstrate that TLR8 engagement represents a mechanism via which CD14 + CD16 + monocytes selectively detect viable as opposed to dead microorganisms, and signal this via producing IL‐1β, which activates T follicular helper cells.…”
Section: Discussionmentioning
confidence: 99%
“…Others show that IL-1b, produced by monocytes downstream of TLR signalling and inflammasome activation, induces differentiation of T follicular helper cells, which augment antibody production. 37 Moreover, Ugolini et al 38 demonstrate that TLR8 engagement represents a mechanism via which CD14 + CD16 + monocytes selectively detect viable as opposed to dead microorganisms, and signal this via producing IL-1b, which activates T follicular helper cells. Similarly, Kwissa et al 21 found that CD14 + CD16 + monocytes, which are induced by dengue virus infection, and by R848 but not CpG, enhance B-cell differentiation, providing another possible explanation for the differential role of monocytes in R848-versus CpG-stimulated B-cell differentiation.…”
Section: Monocytesmentioning
confidence: 99%
“…TLRs 7 and 8 are implicated in the recognition of naturally derived uridineerich ssRNAs of influenza and HIV [36]. In addition TLR7 and TLR8 recognize bacterial RNA [51,64]. Furthermore, TLR7 and 8 are expressed in human plasmacytoid DCs (pDCs), in T and B cells, monocytes and macrophages [65,66].…”
Section: Adjuvant Strategiesmentioning
confidence: 99%
“…Recently, Zhang et al identified, for the first time, human TLR8 small antagonist molecules with a novel inhibition mechanism [304]. SAR studies on the pyrazolo[1,5-a]pyrimidine series led to identification of the compound: CU-CPT8m (64), which proved to be the most active with an IC50 of 67 nM and a strong ability to inhibit the production of pro-inflammatory cytokines (Fig. 34).…”
Section: Bicycles Analoguesmentioning
confidence: 99%
“…Unlike TLR7, TLR8 activation mainly results in the production of inflammatory cytokines due to the types of cells in which it is expressed. A recent study demonstrated that recognition of live bacteria by TLR8 induced human monocytes to produce large amounts of IL-12, which drives a follicular helper T-cell response in naive human CD4 + T cells [85]. …”
Section: Antiviral Immunity Mediated By Rna Sensorsmentioning
confidence: 99%